Effect of Mixed Traffic Platooning by Commercial Vehicle Types on Traffic Flow Characteristics of Highways - Singh, Sandeep; Rajesh, Vidya; Santhakumar, Selvaraj Moses (Periodica Polytechnica Transportation Engineering, 2022)
The existence of different types of Commercial Vehicles (CVs) in the shared roadway affects traffic flow characteristics differently from other vehicles. Owing to the uncertain placement and movement of these CVs in both longitudinal and lateral directions, the opportunities for lane changing and overtaking by other vehicles with lower maneuverability decrease, resulting in the formation of platoons. The study's primary aim is to assess the effect of mixed traffic platoons formed by three different classes of CVs on highway traffic speed, flow, and density under two different traffic regimes (regimes A and B). In this study, regime A represents the non-platooning condition, and regime B represents the platooning condition. Bi-directional traffic data was collected from the highway sections in India using an Infra-Red sensor-based device. The critical leading time headway is determined for the different CVs (platoon leaders) based on the mean absolute relative speed of platoons. The speed-flow-density plots are established using the macroscopic fundamental diagrams for the highway sections under regimes A and B to quantify the platooning impacts of CVs on the traffic characteristics. The study findings reveal that the speed at capacity, density at capacity, and traffic capacity decreased significantly due to CVs' influence on the general traffic mix during the mixed traffic platooning conditions. However, this effect was found to be relatively higher during the Heavy Commercial Vehicle operation as a platoon leader compared to Medium Commercial Vehicle and Light Commercial Vehicle as a platoon leader.